2017
DOI: 10.1016/j.schres.2017.05.003
|View full text |Cite
|
Sign up to set email alerts
|

An emerging role for mitochondrial dynamics in schizophrenia

Abstract: Abnormal brain development has long been thought to contribute to the pathophysiology of schizophrenia. Impaired dendritic arborization, synaptogenesis, and long term potentiation and memory have been demonstrated in animal models of schizophrenia. In addition to aberrant nervous system development, altered brain metabolism and mitochondrial function has long been observed in schizophrenic patients. Single nucleotide polymorphisms in the mitochondrial genome as well as impaired mitochondrial function have both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(41 citation statements)
references
References 110 publications
(125 reference statements)
2
39
0
Order By: Relevance
“…Mitochondrial function is regulated in response to a cell’s metabolic demand, but also through neurotransmission, and plays a critical role in development, synapse formation, and plasticity of spines and synapses [ 99 , 101 , 102 ]. As discussed before, Robicsek and coworkers [ 78 ] reported that SCZ iPSCs were impaired in dopaminergic differentiation and glutamatergic maturation.…”
Section: Introductionmentioning
confidence: 99%
“…Mitochondrial function is regulated in response to a cell’s metabolic demand, but also through neurotransmission, and plays a critical role in development, synapse formation, and plasticity of spines and synapses [ 99 , 101 , 102 ]. As discussed before, Robicsek and coworkers [ 78 ] reported that SCZ iPSCs were impaired in dopaminergic differentiation and glutamatergic maturation.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequent decreases in synaptic mitochondrial and GABA receptors would then reflect homeostatic plasticity downstream of this decreased excitatory drive. Alternatively, presynaptic mitochondria are essential for bouton development (58) and activity (59). Thus, altered mitochondrial transport to the presynaptic compartment could also contribute to synaptic pathology in Sz.…”
Section: Synaptosome Mitochondrion and Postsynaptic Membrane Proteinsmentioning
confidence: 99%
“…Mitochondrial dynamics comprises such processes as mitochondrial fission, fusion, transport within the cell, and mitophagy [106, 107]. Intact mitochondrial dynamics has been linked to normal brain development, while impaired dynamics leads to neuronal injury and developmental dysfunction [108].…”
Section: Mitochondrial Pathwaysmentioning
confidence: 99%
“…The kinesin-related protein 5 family (KIF5A–C) comprises specific motor proteins that are thought to play a vital role in the transport of mitochondria in the nervous system. Mutations in the genes encoding KIF5A–C have been implicated in a host of neurodevelopmental disorders [115-122], as summarized by Flippo and Strack [107]; however, it is unclear whether these derive from impaired mitochondrial transport or from impaired transport of other organelles via KIF5. Interestingly, KIF5A interacts with DISC1 (disrupted in schizophrenia 1), a protein whose namesake highlights its relation to SCZ and other psychiatric disorders [123, 124].…”
Section: Mitochondrial Pathwaysmentioning
confidence: 99%
See 1 more Smart Citation